2020
DOI: 10.1111/jgh.15036
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tenofovir versus entecavir on reducing incidence of hepatocellular carcinoma in chronic hepatitis B patients: A systematic review and meta‐analysis

Abstract: Background and Aim: Studies had shown that tenofovir (TDF) and entecavir (ETV) are widely used as the first-line therapy to inhibit hepatitis B virus replication, which can reduce the risk of hepatocellular carcinoma (HCC) in chronic hepatitis B (CHB) patients, but it was unclear which nucleos(t)ide analogue was most effective. Therefore, we performed a meta-analysis and a systematic review to compare the incidence of HCC in CHB patients who are either on TDF or ETV. Methods: For this study, the following data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Lastly, most of the meta-analyses 36,[41][42][43][44] , but not all 34 , in this comparison exhibited superior chemo-preventive effect by TDF treatment compared to ETV treatment. Since metaanalysis collects numerous studies of the same topic, it is able to show a real difference that was not either statistically significant or captured due to small sample size in individual studies, if the real difference still exists.…”
Section: Discussionmentioning
confidence: 81%
“…Lastly, most of the meta-analyses 36,[41][42][43][44] , but not all 34 , in this comparison exhibited superior chemo-preventive effect by TDF treatment compared to ETV treatment. Since metaanalysis collects numerous studies of the same topic, it is able to show a real difference that was not either statistically significant or captured due to small sample size in individual studies, if the real difference still exists.…”
Section: Discussionmentioning
confidence: 81%
“…Although Table suggests conflicting results between the meta-analyses, with some reporting significant differences between TDF and ETV and others reporting non-significant differences, these conclusions rely on a discretionary framework of statistical significance testing, which has been the subject of much debate in recent years. As an example of the limitations of this framework, three of the meta-analyses reported p values between 0.04 and 0.041; 5,7,8 should the significance threshold (which is set by convention at p<0.05 and is in fact arbitrary) have been altered (e.g. to p<0.01), these meta-analyses could have all concluded a lack of evidence to suggest a difference in HCC risk between the treatments.…”
Section: Interpretation Of Statistical Significance Testing Resultsmentioning
confidence: 99%
“…4 However, the relative effectiveness of these therapies in reducing HCC risk in CHB patients remains an outstanding question; between December 2019 and November 2020, 9 meta-analyses were published comparing HCC risk between ETV and TDF treatment (Table 1). [5][6][7][8][9][10][11][12][13] Despite the metaanalyses including similar primary studies (Supplementary Table 1), they differ in the statistical significance of their results and their clinical interpretation. While some authors concluded that TDF is associated with a lower risk of HCC than ETV and should be the preferred treatment for CHB, others concluded that the risk of HCC is broadly similar between TDF and ETV.…”
Section: Introductionmentioning
confidence: 99%
“…Data from each study were independently extracted by two researchers, using a pre-designed data extraction table. In case of disagreements, a third researcher was invited to reach a majority opinion [ 13 ]. The recorded information included baseline characteristics such as author, year of publication, tumor type, study type, therapeutic regimen, and sample size, as well as survival outcomes including OS, PFS, and adverse events (AEs).…”
Section: Methodsmentioning
confidence: 99%